ADAT ISTIADAT PERKAWINAN MASYARAKAT MELAYU PADA MASA KESULTANAN SIAK - Zulfa, Zulfa (Jurnal Ilmu Budaya, 2010)
This writing aims to describe the investigation on the traditional ways of marriage conducted by Malay people in Siak Regency.